Genetic contribution of suppressor of cytokine signalling polymorphisms to the susceptibility to infection after traumatic injury. (9th September 2018) - Zhang, A; Gu, W; Lu, H; Zeng, L; Zhang, L; Du, D; Hao, J; Wen, D; Wang, X; Jiang, J
Summary: Suppressor of cytokine signalling (SOCS) proteins are crucial negative regulators in many signalling pathways and are implicated in the pathogenesis of infectious diseases. The purpose of this study was to uncover possible associations of common polymorphisms within SOCS genes with infectious outcomes after traumatic injury. A total of 1087 trauma patients (Chongqing cohort 806 and Yunnan cohort 281) were recruited and followed-up for the development of infectious outcomes, such as sepsis and multiple organ dysfunction syndrome (MODS). Twelve selected single nucleotide polymorphisms (SNPs) were screened by pyrosequencing to determine their genotypes and associations with infectious complications. Among the 12 selected SNPs, only the cytokine-inducible Src homology (SH2) domain protein (CISH) promoter rs414171 polymorphism was found consistently to be associated statistically with the incidence of sepsis and MOD score in the two cohorts, despite analysing the SNPs independently or in combination. Further, patients with a T allele had significantly lower CISH expression and lower production of tumour necrosis factor (TNF)-α, but higher production of interleukin (IL)-10. Luciferase assay confirmed that the A→T variant in the rs414171 polymorphism inhibited the transcriptional activities of the CISH gene significantly. The CISH rs414171 polymorphism is associated significantly with susceptibility to sepsis and MODS in traumatic patients, which might prove to be a novel biomarker for indicating risk of infectious outcomes in critically injured patients. Graphical Abstract: